Conception des équipements de travail et prévention des TMS Complémentarités et points d’ancrage des démarches - Jacques Marsot; Jean-Jacques Atain-Kouadio (Perspectives Interdisciplinaires sur le Travail et la Santé)
After a brief reminder about MSD prevention and work equipment design, this article discusses the difficulties observed in combining them. It then proposes “anchor” points that guide, within a participative and multidisciplinary framework, the time spent looking for solutions and decisions. The interactions between the participants facilitate the sharing of reference tools and clarify the decision-making processes. They work as a “methodological engine” that incorporates the issue of MSDs at each design step.This approach should make it possible for companies (SMEs) to find answers to their MSD prevention needs very early in the work equipment design process. It contributes to a better understanding of the levers that make it easier to take MSDs into account and to the development of new standards in the design process.